2015
DOI: 10.1152/ajpregu.00026.2015
|View full text |Cite
|
Sign up to set email alerts
|

Arterial baroreceptor reflex control of renal sympathetic nerve activity following chronic myocardial infarction in male, female, and ovariectomized female rats

Abstract: Pinkham MI, Whalley GA, Guild SJ, Malpas SC, Barrett CJ. Arterial baroreceptor reflex control of renal sympathetic nerve activity following chronic myocardial infarction in male, female, and ovariectomized female rats. Am J Physiol Regul Integr Comp Physiol 309: R169-R178, 2015. First published May 20, 2015 doi:10.1152/ajpregu.00026.2015.-There is controversy regarding whether the arterial baroreflex control of renal sympathetic nerve activity (SNA) in heart failure is altered. We investigated the impact of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 64 publications
3
7
0
Order By: Relevance
“…In OVX group, MAP and HR were not altered; despite that this group had reduced BRS, similar results were observed by Pinkham et al . There were no changes in MAP or HR in OVX + MT group corroborating another study that demonstrated that replacement of testosterone did not increase blood pressure in hypogonadal men .…”
Section: Discussionsupporting
confidence: 87%
“…In OVX group, MAP and HR were not altered; despite that this group had reduced BRS, similar results were observed by Pinkham et al . There were no changes in MAP or HR in OVX + MT group corroborating another study that demonstrated that replacement of testosterone did not increase blood pressure in hypogonadal men .…”
Section: Discussionsupporting
confidence: 87%
“…The baroreflex system is devoted to maintaining cardiovascular homeostasis and preserving blood flow to vital organs (12). In MI, there appears to be a direct relationship between baroreflex sensitivity and survival, reduced survival having been reported in the setting of reduced baroreflex function (17,39). It is known that eNOS activity is impaired in endothelial cells exposed to native LDL (18).…”
Section: Discussionmentioning
confidence: 99%
“…In the Lewis Polycystic Kidney rat model of CKD, reflexive renal sympathoinhibition following vagal nerve stimulation was blunted in females but not males (Salman et al, 2017). Work by the Barret group has demonstrated that biological sex influences baroreflex control of renal sympathetic nerve activity following myocardial infarction (Pinkham et al, 2015), and that female rats have attenuated renal sympathetic nerve activation in the minutes following myocardial infarction relative to males (Pinkham et al, 2012). These studies, along with the known contribution of biological sex towards autonomic control of blood pressure warrant further investigation into circadian autonomic control of renal function.…”
Section: Sex Differencesmentioning
confidence: 99%